Alteration of Ictal and Interictal Perfusion in Patients with Paroxysmal Kinesigenic Dyskinesia - Kim, Y.-D; Kim, J.-S; Chung, Y.-A; Song, I.-U; Oh, Y.-S; Chung, S.-W; Kim, H.-T; Kim, Y.-I; Lee, K.-S (Neuropediatrics, 2011)
Although previous cerebral blood flow studies have suggested that the basal ganglia or thalamus are involved in the pathogenesis of paroxysmal kinesigenic dyskinesia (PKD), the precise anatomic substrate or pathophysiological networks associated with PKD remain unclear. Here, ictal and interictal single photon emission computed tomography (SPECT) in 2 patients with idiopathic PKD compared to 6 age-matched normal controls and the perfusion findings of subtraction ictal SPECT co-registered to MRI (SISCOM) in 1 patient are reported. The interictal and ictal perfusion changes were different in each of the patients and there were no consistent anatomic substrates observed. 2 patients had significant perfusion changes in the left frontal/temporal cortices compared to controls, whereas the others showed an increased uptake of 99mTc-ethyl cysteinate dimer (ECD) in the left occipital area on subtraction SPECT imaging. The results of this study suggest that the pathophysiology of PKD cannot be simply explained by lesions of the basal ganglia or thalamus, and that other associated areas of the cortex are likely involved in these movement disorders.
Keywords: paroxysmal kinesigenic dyskinesia (PKD); cerebral blood flow; SPECT